2019
DOI: 10.1186/s12906-019-2775-2
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of migraines with Tianshu capsule: a multi-center, double-blind, randomized, placebo-controlled clinical trial

Abstract: BackgroundTianshu capsule (TSC), a formula of traditional Chinese medicine, has been widely used in clinical practice for prophylactic treatment of headaches in China. However, former clinical trials of TSC were small, and lack of a standard set of diagnostic criteria to enroll patients. The study was conducted to re-evaluate the efficacy and safety of TSC post-marketing in an extending number of migraineurs who have diagnosed migraine with the International Classification of Headache Disorders, 3rd edition (b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(19 citation statements)
references
References 15 publications
(14 reference statements)
0
19
0
Order By: Relevance
“…Six RCTs reported outcomes at the end of the 4-week follow-up phase (26,27,31,34,39,41). Fourteen RCTs reported data on the primary outcome measure (migraine frequency) at the EoT (25-29, 31, 34, 35, 37, 39-42) and six reported this at the EoFU (26,27,31,(39)(40)(41). The number of RCTs that reported secondary outcomes such as migraine days, pain VAS/NRS, migraine duration, frequency of acute medication, and the response rate was <10.…”
Section: Characteristics Of the Included Rctsmentioning
confidence: 99%
See 1 more Smart Citation
“…Six RCTs reported outcomes at the end of the 4-week follow-up phase (26,27,31,34,39,41). Fourteen RCTs reported data on the primary outcome measure (migraine frequency) at the EoT (25-29, 31, 34, 35, 37, 39-42) and six reported this at the EoFU (26,27,31,(39)(40)(41). The number of RCTs that reported secondary outcomes such as migraine days, pain VAS/NRS, migraine duration, frequency of acute medication, and the response rate was <10.…”
Section: Characteristics Of the Included Rctsmentioning
confidence: 99%
“…The methodological quality of included RCTs was assessed using the Cochrane Collaboration risk of bias tool and presented in Figure 2. Regarding the random sequence generation, 11 RCTs were assessed as "low risk" for performing adequate randomization (25,26,28,31,32,(36)(37)(38)(39)(40)(41), the remaining seven RCTs were "unclear" due to lack of information (27,29,30,(33)(34)(35)42). Six RCTs depicted the allocation concealment method and were assessed as "low risk" for this domain (26,28,(37)(38)(39)(40), the remaining 12 studies were evaluated as "unclear" due to the absence of relevant information.…”
Section: Risk Of Bias Assessmentmentioning
confidence: 99%
“…Before this study, there were many similar types of research on the treatment and prevention of migraine in TCM, with pros and cons. A multicenter double-blind, randomized, placebo-controlled clinical trial demonstrated that Tianshu capsule (TSC), a formula of traditional Chinese medicine, could decrease the frequency and days of migraine and improve related symptoms with good safety [ 24 ]. In this trial, primary and second outcomes included only the directly related indicators of headache, such as headache frequency, VAS, and number of onset days, while evaluation of mood, sleep status, quality of life, and disability status was lacking.…”
Section: Discussionmentioning
confidence: 99%
“…Chinese herbal medicine (CHM), which is often prescribed to migraine patients in China [25], has gained clinical research evidence as an effective alternative or complementary therapy for migraine in recent years. However, most of the existing evidence has been generated from randomised controlled trials (RCTs) [26][27][28][29][30] and RCT-based systematic reviews [31][32][33][34]. Under controlled settings, RCTs usually apply strict selection criteria and provide unified treatments to all participants [35].…”
Section: Introductionmentioning
confidence: 99%